2021
DOI: 10.3844/ajbbsp.2021.241.247
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents, Antibacterial and Coagulation Activity of the Essential Oil from the Stem of Artemisia argyle H. Lév.

Abstract: Artemisia argyle H. Lév. (A. argyle) is a plant of historical importance known as the "mother of herbs" in the Middle Ages. As the leaves of A. argyle have been studied more, but the stems has not been reported. This paper explores the chemical constituents, antibacterial and coagulation activities of the Essential Oil from the Stems of A. argyle (EOSAA) for better exploitation and utilization of resources. EOSAA was extracted by hydrodistillation and its chemical constituents were determined by GC-MS. Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…The present research found 1.3 to 1.9% essential oil in the leaves, which is higher than the contents being between 0.2 and 0.7% for aerial parts as reported by various authors [6,8,9,[14][15][16][17][18]. Most authors report 1,8-cineole as the major compound, and camphor, borneol, terpinen-4-ol and α-terpineol were also present in most samples.…”
Section: Discussioncontrasting
confidence: 58%
“…The present research found 1.3 to 1.9% essential oil in the leaves, which is higher than the contents being between 0.2 and 0.7% for aerial parts as reported by various authors [6,8,9,[14][15][16][17][18]. Most authors report 1,8-cineole as the major compound, and camphor, borneol, terpinen-4-ol and α-terpineol were also present in most samples.…”
Section: Discussioncontrasting
confidence: 58%